Implementing IPv6 as a Peer-to-Peer Overlay Network - Zhou, Lidong; Renesse, Robbert van; Marsh, Michael (Proceedings of Workshop on Reliable Peer-to-Peer Distributed Systems (RPPDS '02), 2002)
This paper proposes to implement an IPv6 routing infrastructure as a self-organizing overlay network on top of the current IPv4 infrastructure. The overlay network builds upon a distributed IPv6 edge router with a master/slave architecture. We show how different slaves can be constructed to tunnel through NATs and firewalls, as well as to improve the robustness of the routing infrastructure and to provide efficient and resilient implementations for features such as multicast, anycast, and mobile IP, using currently available peer-to-peer (P2P) protocols. The resulting IPv6 overlay network would restore the end-to-end property of the original Internet, support evolution and dynamic updating of the protocols running on the overlay network, make available IPv6 and the associated features to network applications immediately, and provide an ideal underlying infrastructure for P2P applications, without changing networking hardware and software in the core Internet.